Are school-based violence prevention interventions inclusive and effective for children with disabilities? A systematic review of global evidenceResearch in context - Emily Eldred; Karen Devries; Anja Zinke-Allmang; Rizwana Mallick; Waliyah Mughis; Lena Morgon Banks; Amiya Bhatia (EClinicalMedicine)
Summary: Background: Children with disabilities are twice as likely to experience violence compared to peers without disabilities. While evaluations of school-based interventions targeting the prevention of violence against children in schools are growing in number, it is unclear whether these interventions are inclusive of, or effective for, children with disabilities. Methods: We searched six databases (Medline, Cochrane Library, Embase, Global Health, PsycINFO, Web of Science) and utilised professional networks to identify systematic reviews which included randomised controlled trials (RCTs) of school-based violence prevention interventions up to May 2024. Once we identified our final sample of systematic reviews (n = 29) we hand searched the included papers within these reviews and included all RCTs of school-based violence prevention interventions. We applied criteria to assess disability inclusion and conducted a narrative synthesis of study characteristics, adaptations to intervention and/or data collection design, and effect estimates. We assessed risk of bias using the Cochrane Risk of Bias tool. This review was registered on PROSPERO (CRD42023463384). Findings: We identified 160 articles of school-based violence prevention interventions. Of these, 13 articles reporting on 10 trials (8.13%) explicitly mentioned disability: 3/10 trials reported on the magnitude of intervention effects among children with disabilities; 4/10 trials mentioned adaptations to research or intervention design to include children with disabilities; 6/10 trials mentioned disability as part of the sample characteristics but did not report further sub-group analysis. 3 trials were effective in reducing violence in schools for children with disabilities, with risk of bias ranging from ‘low’ (n = 1) to ‘some concerns’ (n = 2). Interpretation: Despite growing evidence on how to prevent school violence, there is limited research on the effect of such interventions for children with disabilities. There is a need for future evaluations to stratify effects by disability, conduct disability-inclusive research, and tailor interventions for children with disabilities. Funding: This research was partially funded by the Foreign, Commonwealth and Development Office under the PENDA project (PO8073).